Updated history of pisco - Ernesto Ramírez (2025)
The document examines the origin and evolution of pisco, highlighting its history from the cultivation of grapevines in Peru and Chile during the 16th century. Peru, benefiting from favorable climatic conditions, recorded the first South American wine in 1539, while Chile documented the distillation of aguardiente (a grape spirit) as early as 1586. However, the authenticity of some Chilean records is questioned due to a lack of documented evidence. The name “pisco” comes from the Peruvian region of Pisco, known for its birds and port, where the spirit was stored in clay jars called “piscos.” Peruvian documents from 1613 and 1712 confirm the early use of the term, while Chile adopted the name centuries later—even renaming a town “Pisco Elqui” in 1936 to legitimize its production. The dispute over the spirit’s designation of origin intensified with research showing Peru’s historical exports of pisco to markets like Guatemala and Chile. Although Chile developed its own industry, 19th-century Chilean lexicographers acknowledged the Peruvian origin of pisco. The document concludes that, beyond the controversy, ongoing research enriches both the history and quality of this distilled spirit.